Kebangkitan Rohani : Sejarah dan Pengaruh Gerakan Pentakosta di Era Modern (International Forum of Researchers and Lecturers, 2024)
This article discusses the spiritual revival triggered by the Pentecostal Movement in the modern era, focusing on its history, development, and impact on society. Through literature analysis, this study identifies the increase in worship participation, profound spiritual experiences, and significant social engagement within Pentecostal communities. Additionally, cultural adaptation and the use of technology in worship practices are also important factors in the growth of this movement. Despite facing challenges and criticism, the Pentecostal Movement shows potential to continue contributing to spiritual and social life. This research aims to provide insights into the relevance and impact of the Pentecostal Movement in contemporary society.